Closing the Loop Enabling EV Battery Circularity through Data Transparency - Sveinbjörnsson, Ágúst Heiðar; Vejrangsi, Paritchaya (My University, 2025)
The transition to electric vehicles (EVs) is rapidly accelerating in Europe due to the climate targets and growing demand for sustainable transformation. The rise in EV adoption is increasing the number of batteries reaching end-of-life (EoL), which causes various challenges such as inefficiencies, waste, and safety risks. These issues result from a lack of alignment across the value chain. This thesis aims to address this misalignment by investigating three research questions: (1) identifying the state-of-art of EoL processes and the its challenges associated with product and data problems, (2) exploring tools and mechanisms enabling data exchange to mitigate these problems, and (3) demonstrating how Battery-as-a-service (BaaS) business model can incentivize data sharing through the identified tools and mechanisms. The thesis applies various qualitative methods, including a systematic literature review, semi-structured interviews with industry experts, and workshops to collect the data. The findings show that the main barriers to effective EoL management stem from uncircular product designs and limited. data transparency across the value chain. Several tools and mechanisms for enhancing data transparency were identified and evaluated using the SWOT framework. The BaaS model was examined through the Circular Business Model Canvas (CBMC) and System Dynamics (SD) modelling, which helped visualize incentive structures for circular designs and collaborations. Future research should acknowledge that these results are based on the current industry, which is subject to change due to high industry uncertainties and fast-spaced developments. Engaging a more diverse group of stakeholders from diverse regions could also strengthen validity of findings. Moreover, key elements of the BaaS model require in-depth analysis to determine their viability and feasibility indifferent market environments at scale. Finally, quantifying and contextualizing the SD model can provide a strong basis for strategic decision-making.
Keywords: Electric Vehicles; Electric Vehicle Batteries; Circular Economy; Design for Circularity; End-of-Life Management; Battery Disassembly; Data Exchange; Battery-as-a-Service